2010
DOI: 10.1098/rstb.2010.0005
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of evolutionary change in gene expression levels

Abstract: The regulation of gene expression is an important determinant of organismal phenotype and evolution. However, the widespread recognition of this fact occurred long after the synthesis of evolution and genetics. Here, we give a brief sketch of thoughts regarding gene regulation in the history of evolution and genetics. We then review the development of genome-wide studies of gene regulatory variation in the context of the location and mode of action of the causative genetic changes. In particular, we review map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 80 publications
(137 reference statements)
4
53
0
Order By: Relevance
“…Studying the nature of the regulatory changes ( cis- or trans- acting) that underlie parental divergence and transgressive hybrid segregation can provide insight into the evolutionary forces that influence gene expression variation within and between populations (Lemos et al 2008; Emerson and Li 2010). There is ongoing debate over the relative importance of cis - and trans -regulatory mutations in terms of their contributions toward adaptive evolution (Hoekstra and Coyne 2007; Prud’homme et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the nature of the regulatory changes ( cis- or trans- acting) that underlie parental divergence and transgressive hybrid segregation can provide insight into the evolutionary forces that influence gene expression variation within and between populations (Lemos et al 2008; Emerson and Li 2010). There is ongoing debate over the relative importance of cis - and trans -regulatory mutations in terms of their contributions toward adaptive evolution (Hoekstra and Coyne 2007; Prud’homme et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…First, genome-wide allele-specific mRNA expression analyses have revealed that both cis - and trans -regulatory changes contribute to differential expression of mRNAs among closely related species [32-34]. Small RNAs can act as trans -regulatory factors, which contribute to differential mRNA expression [35].…”
Section: Introductionmentioning
confidence: 99%
“…Studying cis -regulatory elements has been of great interest over the last years as it has been suggested that phenotypic changes also result from variation in these regions rather than in coding regions [2,81,82]. A relatively straightforward way to investigate this is to first analyze sequence variation and search for specific motifs in promoter regions [83].…”
Section: Discussionmentioning
confidence: 99%